2018
DOI: 10.1002/cpe.4793
|View full text |Cite
|
Sign up to set email alerts
|

Detecting misinformation in social networks using provenance data

Abstract: Summary In recent years, the credibility of information on social networks has attracted considerable of interest due to its critical role in the spread of information online. In this paper, we argue that the quality of information created on social networks can be analyzed using its provenance data. In particular, we propose an algorithm that assesses information credibility on social networks in order to detect fake or malicious information using a fuzzy analytic hierarchy process to assign proper weights to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…They concluded that the bitmap indexing technique was the appropriate choice for the data warehouse query operation 20 . There are also studies on provenance data suitable for the encoded bitmap index due to its often unchanging feature 21 . Abdulhadi et al measured the performance of bitmap indexes by comparing it with the B‐tree indexes using the Oracle environment that utilizes B‐tree as the default indexing.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that the bitmap indexing technique was the appropriate choice for the data warehouse query operation 20 . There are also studies on provenance data suitable for the encoded bitmap index due to its often unchanging feature 21 . Abdulhadi et al measured the performance of bitmap indexes by comparing it with the B‐tree indexes using the Oracle environment that utilizes B‐tree as the default indexing.…”
Section: Related Workmentioning
confidence: 99%
“…We observe the use of complex event processing techniques in different domains. This technique is used to detect patterns in different domains such as social media [19][20][21][22], internet of things [23][24], cloud computing [25], ecommerce [26] and real time streaming based applications [27]. Our study focuses on detecting predefined patterns within the data collected from the clickstream data generated by user-system interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CDR data has been impactful in the analysis of varying models and its application is growing exceedingly. Among these usages, urban sensing and planning [8], [9], traffic engineering [10], [11], predicting energy consumption [12], improved churn prediction using both CDR data and community detection [13] [14]- [22]. Provenance graph is mainly used to understand the data lineage.…”
Section: Literature Reviewmentioning
confidence: 99%